Social Studies Teachers’ Conceptualizations and Practices of Democracy in Upper Classes in Primary Schools in Botswana - Mhlauli, Mavis B. (Advances in Social Sciences Research Journal, 2016)
The purpose of this study was to interrogate the social studies teachers’ conceptualizations and practices on democracy in upper classes in primary schools in Botswana. The study was undertaken in upper classes in six primary schools in Botswana for a period of three months.  The theoretical underpinnings of my study are based on what Asante (2010) refers to as Afrocentricity, which basically focuses on relocating the African people historically, socially, economically, politically and philosophically in an effort to decolonize their minds. For its methodology, the study was qualitative in nature and used the naturalistic inquiry paradigm. Data were collected through interviews, participant observations and focus group discussions. Data were analyzed using the constant comparative technique. The findings of the study revealed that even though teachers conceptualize democracy from a liberal point of view, they seem to be moving the center as they also take into account the contextual and socio-cultural factors. The conclusion drawn from this study is that teachers have a deep understanding of democracy, however, lack pedagogical content knowledge of democracy. The study recommends that teachers be constantly in-serviced on how to develop practical skills when teaching topical issues like democracy as they contribute directly towards they type of citizens they produce.